A.K. Fisher papers - Fisher, A. K. (Albert Kenrick), 1856-1948.; Fisher, Anne B. (Anne Benson), 1898-; Fisher, Walter K. (Walter Kenrick), 1878-1953.
Correspondence, letterbooks, memoranda, diaries, speeches, articles, reports, field notes and records, family papers, newspaper clippings, scrapbooks, printed matter, maps, drawings, photographs, and other papers relating chiefly to Fisher's activities as an ornithologist and vertebrate zoologist. Documents an expedition (1891) to Death Valley; biological surveys (1892-1898) in Arizona, California, Nevada, New Mexico, Utah, and other western areas; the Harriman Alaska Expedition (1899); and Pinchot South Sea Expedition (1929). Also documents Fisher's association with the American Ornithologists' Union, U.S. Biological Survey, and Washington Biologists' Field Club. Subjects include conservation, forestry, game laws, and wildlife conservation. Family papers include those of Fisher's son, Walter K. Fisher, naturalist and artist; and daughter-in-law, Anne B. Fisher, author.
Correspondents include Frank M. Chapman, Louis Agassiz Fuertes, Ben Lilly, Edgar Alexander Mearns, C. Hart Merriam, Gifford Pinchot, Robert Ridgway, Witmer Stone, and Alexander Wetmore.
Botanist, naturalist, and zoologist.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Chapman, Frank M. -- 1864-1945 -- Correspondence; Fuertes, Louis Agassiz, -- 1874-1927 -- Correspondence; Lilly, Ben, -- 1856-1936 -- Correspondence; Mearns, Edgar Alexander, -- 1856-1916 -- Correspondence; Merriam, C. Hart -- 1855-1942 -- Correspondence; Pinchot, Gifford, -- 1865-1946 -- Correspondence; Ridgway, Robert, -- 1850-1929 -- Correspondence; Stone, Witmer, -- 1866-1939 -- Correspondence; Wetmore, Alexander, -- 1886-1978 -- Correspondence; Fisher family; United States. -- Bureau of Biological Survey; American Ornithologists' Union; Washington Biologists' Field Club; Biology -- Washington (D.C.) -- Societies, etc; Biology -- West (U.S.); Conservation of natural resources; Forests and forestry; Game laws; Ornithology; Ornithology -- Societies, etc; Scientific expeditions -- Alaska; Scientific expeditions -- Oceania; Scientific expeditions -- West (U.S.); Wildlife conservation; Zoology; Alaska -- Discovery and exploration; Death Valley (Calif. and Nev.) -- Discovery and exploration; Oceania -- Discovery and exploration; West (U.S.) -- Discovery and exploration; Botanists; Naturalists; Zoologists